1963
DOI: 10.1111/j.1365-3091.1963.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

A Graphic Presentation of the Facies Model of Salt Marsh Deposits

Abstract: Salt marsh deposits are developed along many tidal flat areas, lagoons, bays, etc. They are characterized by small thickness, special sedimentary structures, high organic content, growth of phanerogamous halophytes, and often by scarcity or absence of microfauna. A graphical representation of a section at Ameland (The Netherlands) is given, as well as radiographs of a sandy (Ameland) and a clayey (California) marsh sample. Little structural difference exists between the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
193
0
8

Year Published

1964
1964
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(204 citation statements)
references
References 9 publications
3
193
0
8
Order By: Relevance
“…"Sediment," whether allochthonous or autochthonous, carries no connotation of an underlying parent material and therefore seems to be the preferable term. Bouma (1963), Macdonald (1977b), and others have suggested that salt marsh substrates contain finer, more poorly sorted sediments than any other intertidal environment. Such generalities, however, tend to disregard the subfacies developed within salt marshes as well as the relationship between marsh substrates and those in closely adjacent habitats.…”
Section: Characteristic Sedimentsmentioning
confidence: 96%
See 2 more Smart Citations
“…"Sediment," whether allochthonous or autochthonous, carries no connotation of an underlying parent material and therefore seems to be the preferable term. Bouma (1963), Macdonald (1977b), and others have suggested that salt marsh substrates contain finer, more poorly sorted sediments than any other intertidal environment. Such generalities, however, tend to disregard the subfacies developed within salt marshes as well as the relationship between marsh substrates and those in closely adjacent habitats.…”
Section: Characteristic Sedimentsmentioning
confidence: 96%
“…2 Specifically excluded are unvegetated intertidal areas, such as ordinary mud and sand flats, as well as subtidal vegetated substrates, such as Zostera and Thalassia bec:ls. This distinction seems obvious by traditional American usage, yet many European conventions differ; Dutch "salt marshes" are considered to be predominantly supratidal, for example, whereas less distinction is made between vegetated and unvegetated intertidal flats (van Straaten and Kuenen, 1957;Bouma, 1963;Beeftink, 1966).…”
Section: Definition and Occurrences Of Coastal Salt Marshesmentioning
confidence: 97%
See 1 more Smart Citation
“…Such a slice was thinned down to 9-18 mm, and then an X-ray radiograph was made (HAMBL1N, 1962;CALVERT and VEEVERS, 1962;BOUMA, 1963) (for details see BOUMA, 1964e). In order to obtain a maximum of detail the Kodak Industrial AA type of film was employed.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of prints of X-ray radiographs have been published so far (HAMBLIN, 1962;CALVERT and VEEVERS, 1962;RIOULT et RIBY, 1963;OELE, 1964;BOUMA, 1963BOUMA, , 1964bBOUMA and SHEPARD, 1964;BOUMA and MARSHALL, 1964). …”
Section: Introductionmentioning
confidence: 99%